2006
DOI: 10.1115/1.2264394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Assumed Stiffness and Mass Density on the Impact Response of the Human Chest Using a Three-Dimensional FE Model of the Human Body

Abstract: The mass density, Young's modulus (E), tangent modulus (Et), and yield stress (sigma y) of the human ribs, sternum, internal organs, and muscles play important roles when determining impact responses of the chest associated with pendulum impact. A series of parametric studies was conducted using a commercially available three-dimensional finite element (FE) model, Total HUman Model for Safety (THUMS) of the whole human body, to determine the effect of changing these material properties on the predicted impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…Also, the fracture depended on the ultimate plastic strain value and location. Such simplifications were already used in many other studies (Schileo et al, 2008;Kimpara et al, 2006) and offered acceptable results. Future work could benefit from the implementation of a user pseudo-elasto-plastic material law based on energy formulation that includes unsymmetrical behavior, damage and failure .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Also, the fracture depended on the ultimate plastic strain value and location. Such simplifications were already used in many other studies (Schileo et al, 2008;Kimpara et al, 2006) and offered acceptable results. Future work could benefit from the implementation of a user pseudo-elasto-plastic material law based on energy formulation that includes unsymmetrical behavior, damage and failure .…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, the material rupture is modeled without any damage effect. The plastic strain threshold used in the model is ranged from 1% to 3% (Schileo et al, 2008;Kimpara et al, 2006;Arnoux et al, 2005). Strain-rate dependency of the bone structure was investigated through a sensitivity analysis.…”
Section: Model Descriptionmentioning
confidence: 99%
“…This error is small compared to the effect of the perichondrium (which increases the stiffness of the total structure by an average of 100%; Forman et al, 2010). This error is also small when compared to the spread of costal cartilage modulus values in current whole-body finite models, which range from 9 (Ruan et al, 2003) to 49 MPa (Kimpara et al, 2006).…”
Section: Model Prediction Fitmentioning
confidence: 80%
“…Many current thorax models include homogeneous representations of costal cartilage, with material property definitions derived from local material characterizations (Lee and Yang, 2001;Iwamoto et al, 2002;Kimpara et al, 2006;Wang, 1995). There are, however, at least two types of heterogeneities in costal cartilage that may cause models developed with local material properties to erroneously predict its overall structural behavior.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, Bandak et al [3] have developed a three-dimensional (3D) FE model of the human ankle joint to study the mechanism of impact injury to the major bones of the foot. Kimpara et al [4] have analyzed the impact response of the human chest using a 3D FE model of the human body. Highly biofidelic 3D FE models of the human pubic symphysis have been suggested in [5], while Dakin et al [6] have reported their experimental measurements of elastic and viscoelastic properties of the human pubic symphysis joint subjected to lateral impact loading.…”
Section: Introductionmentioning
confidence: 99%